2018
DOI: 10.1167/iovs.18-24087
|View full text |Cite
|
Sign up to set email alerts
|

Extended Intravitreal Rabbit Eye Residence of Nanoparticles Conjugated With Cationic Arginine Peptides for Intraocular Drug Delivery: In Vivo Imaging

Abstract: PurposeDrug delivery by intravitreal injection remains problematic, small agents and macromolecules both clearing rapidly. Typical carriers use microparticles (>2 μm), with size-related liabilities, to slow diffusion. We recently described cationic nanoparticles (NP) where conjugated Arg peptides prolonged residence in rat eyes, through ionic interaction with vitreal poly-anions. Here we extended this strategy to in vivo tracking of NP-conjugate (NPC) clearance from rabbit eyes. Relating t1/2 to zeta potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Only particles with a diameter < 510 nm and possessing neural or negative surface charge could diffuse readily into the vitreous body [14,35]. A number of studies have reported that with appropriate size and surface charge, intraocular NPs could gradually spread throughout the retinal layers, and reside there for up to 90 days post-dosing [36][37][38][39]. Our preliminary data demonstrated the successful penetration of TiO 2 -NP from the corneal surface to the posterior region of the eye after topical administration; however, the efficiency Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Only particles with a diameter < 510 nm and possessing neural or negative surface charge could diffuse readily into the vitreous body [14,35]. A number of studies have reported that with appropriate size and surface charge, intraocular NPs could gradually spread throughout the retinal layers, and reside there for up to 90 days post-dosing [36][37][38][39]. Our preliminary data demonstrated the successful penetration of TiO 2 -NP from the corneal surface to the posterior region of the eye after topical administration; however, the efficiency Fig.…”
Section: Discussionmentioning
confidence: 99%